Lymph Node Dissections for T3T4 Stage Penile Cancer Patients Without Preoperatively Detectable Lymph Node Metastasis Bring More Survival Benefits: A Propensity Matching Analysis - Li, Han; Ma, Yucheng; Jian, Zhongyu; Jin, Xi; Xiang, Liyuan; Li, Hong; Wang, Kunjie (Frontiers in Oncology, 2021)
Background & Aims: The current guidelines for the treatment of penile cancer patients with clinically non-invasive normal inguinal lymph nodes are still broad, so the purpose of this study is to determine which patients are suitable for lymph node dissection (LND). Methods: Histologically confirmed penile cancer patients (primary site labeled as C60.9-Penis) from 2004 to 2016 in the Surveillance, Epidemiology, and Results database were included in this analysis. Univariate and multivariate Cox regressions were applied to determine an over-all estimate of LND on overall survival and cancer-specific survival. 1:1 Propensity matching analysis (PSM) was applied to enroll balanced baseline cohort, and further Kaplan-Meier (KM) survival analysis was used to get more reliable results. Results: Out of 4458 histologically confirmed penile cancer patients with complete follow up information, 1052 patients were finally enrolled in this analysis. Age, pathological grade, T stage, LND were identified as significant predictors for overall survival (OS) in the univariate Cox analysis. In the multivariate Cox regression, age, pathological grade, T stage, LND were found significant. The same results were also found in the univariate and multivariate Cox regression for cancer-specific survival (CSS). After the successful PSM, further KM analysis revealed that LND could bring significant OS and CSS benefits for T3T4 patients without lymph node metastasis. Conclusion: Lymph node dissection may bring survival benefits for penile cancer patients without preoperatively detectable lymph node metastasis, especially for T3T4 stage patients. Further randomized control trial is needed.